Risk of Respiratory Infectious Diseases and the Role of Methylphenidate in Children with Attention-Deficit/Hyperactivity Disorder: A Population-Based Cohort Study - Li, Dian-Jeng (Int J Environ Res Public Health, 2021)
Children with attention-deficit/hyperactivity disorder (ADHD) are commonly affected by medical illness. The aim of the present study was to explore the risks of contracting respiratory infectious diseases (RIDs), including upper and lower RIDs and influenza, in children with ADHD. We also examined whether methylphenidate has a protective effect regarding the risk of contracting RIDs among children with ADHD who have a history of methylphenidate treatment. Children in the Taiwan Maternal and Child Health Database from 2004 to 2016 were included in the present study. Upper and lower RIDs, influenza, ADHD, age, sex, and records of methylphenidate prescription were identified. A Cox proportional hazards regression model was used to estimate the significance of the risk of RIDs among children with ADHD in comparison with that among children without ADHD after adjustment for sex and age. The self-controlled case series analysis was conducted to examine the protective effect of methylphenidate treatment against RIDs. In total, 85,853 children with ADHD and 1,458,750 children without ADHD were included in the study. After controlling for sociodemographic variables, we observed that children with ADHD had significantly higher risks of upper RIDs, lower RIDs, and influenza infection than did those without ADHD. Among the children with ADHD who had a history of methylphenidate treatment, the risk of contracting RIDs was lower during the methylphenidate treatment period than during the nontreatment period. Children with ADHD had a higher RID risk than those without ADHD. Methylphenidate might reduce the risk of RIDs among children with ADHD who have a history of methylphenidate treatment.